Faktor Pendorong Resiliensi Perempuan Korban Kekerasan dalam Rumah Tangga (Studi di Kelurahan Giwu dan Kelurahan Saoka Kota Sorong) - Ramli, Umar; Hidaya, Nur; Kamaluddin, Kamaluddin (Universitas Muhammadiyah Sorong, 2023)
Domestic violence is a detrimental social phenomenon that produces negative impacts, particularly on women. This study focuses on the Giwu and Saoka Subdistricts in the city of Sorong to delve into the understanding of the resilience of women who are victims of domestic violence. The research aims to analyze the factors that enable women to endure domestic violence. Employing a qualitative approach, specifically a case study research design, the study utilizes nonprobability sampling, particularly through purposive sampling techniques, with data collection taking place from September to November 2023. Data collection involves observation techniques, in-depth interviews, and literature review. The data analysis process begins with reduction, followed by data presentation, and verification. The research findings indicate that factors driving wives to persist involve emotional aspects such as love and spirituality, while external factors encompass social stigma, economic aspects, and concern for children. These findings highlight the complexity of the resilience of women who are victims of violence, influenced by various internal and external factors.